Pattern of mortality in newborns referred to a tertiary level NICU - Mrinalini Das; Meena Kumari Mili; Monalisa Bhoktiari; Trinayan Mili (New Indian Journal of OBGYN)
Background: Perinatal and neonatal mortality rates are the major determinants of healthcare system. India is one of the largest contributors in the pool of neonatal death in the world. In India data on causes and predictors of neonatal mortality in referral tertiary units is lacking, therefore analysis of pattern of neonatal mortality is of paramount importance in formulating preventive health services. Objectives: 1.To find out the pattern of mortality among the newborns referred to NICU of Department of Paediatrics, GMCH;2.To find out predictors of mortality among these newborns. Methodology: A prospective observational study was done in Gauhati Medical College and Hospital, Guwahati from January 2019 to December 2019. A total of 3491 newborns were consecutively enrolled who were referred from the peripheral SNCU and admitted in outborn neonatal unit based upon the inclusion criteria. Results: Out of 3491 newborns, 770(22%) expired. The most common causes of mortality in our setting were found to be birth asphyxia (50.1%), neonatal sepsis (23.4%), MAS (7.8%), prematurity (7.5%), RDS (7.3%) and congenital malformation (3.9%). It was observed that maximum deliveries 86.4% were institutional, followed by home delivery 12.7% and 0.9% were delivered in ambulance. Maximum mothers 1840 (52.7%) had 4 or more ANC. Neonates referred without treatment had higher death rate 58.6% compared to 10.2% death rate in neonates who were referred with treatment during transport. At the time of admission 56.3% of the babies presenting with hypothermia,61.4% of neonates with hypoglycaemia, 42.2% of neonates with prolonged CRT and 27.8% presenting with hypoxemia expired. Conclusion: Most of the neonatal deaths were because of birth asphyxia therefore proper antenatal checkups and care of women during labour and effective neonatal resuscitation at peripheral health care centres should be given. The second most common cause of death is sepsis therefore health education to the mother regarding antenatal and newborn care and hygiene should be given. Unstable vitals at the time of arrival have higher chances of mortality. So identification of sick neonates and their timely referral should be done early with transport treatment without delay.